Efektivitas Penggunaan Permainan Edukatif Ludo Kimia Sebagai Media Pembelajaran pada Materi Ikatan Kimia Terhadap Hasil Belajar Siswa Kelas X SMAN 1 Lubuk Alung - Ramadhani, Ikhsan (journal of residu, 2019)
This study was backgrounded by the availability of chemistry ludo educative game as learning media on chemical bonding lesson that has not been tested its effectivity to the study result of students. This study aims to reveal the effectivity level of the use of chemistry Ludo Educative Game as Learning Media on chemical bonding lesson to the study result of 10th grade student of SMAN 1 Lubuk Alung. The type of this study is pseudo experiment with non-equivalent control group designas the study design. The populations in this study are the 10th grade student of SMAN 1 Lubuk Alung. The sampling of this study was taken by purposive sampling technique. The class of X MIPA 2 is an experiment class and the class of X MIPA 1 is a control class. The data analysis techniques conducted in this study are N-Gain test and average equality test (t-test). The result of the study showed that there is an understanding improvement in both classes. The experiment class showed better understanding improvement compare to the control class. this is proven by pretest marks of the students in the both class which have 83,61 and 77,88 as the pretest mark. This is also proven by the average value of N-gain test. The experiment class got 0,78 with high category and control class got 0,67 with medium category. It  is also supported by the significant value of t-test for both classes. 0,001< 0,05 (α) is the significant value of t-test which indicates that hypothesis is received. Keywords: Effectivity, Educational Ludo Chemical Games, Chemical Bonding, Learning Outcomes